Accuracy assessment of surgical planning and three-dimensional-printed patient-specific guides for orthopaedic osteotomies. (June 2017) - Sys, Gwen; Eykens, Hannelore; Lenaerts, Gerlinde; Shumelinsky, Felix; Robbrecht, Cedric; Poffyn, Bart
This study analyses the accuracy of three-dimensional pre-operative planning and patient-specific guides for orthopaedic osteotomies. To this end, patient-specific guides were compared to the classical freehand method in an experimental setup with saw bones in two phases. In the first phase, the effect of guide design and oscillating versus reciprocating saws was analysed. The difference between target and performed cuts was quantified by the average distance deviation and average angular deviations in the sagittal and coronal planes for the different osteotomies. The results indicated that for one model osteotomy, the use of guides resulted in a more accurate cut when compared to the freehand technique. Reciprocating saws and slot guides improved accuracy in all planes, while oscillating saws and open guides lead to larger deviations from the planned cut. In the second phase, the accuracy of transfer of the planning to the surgical field with slot guides and a reciprocating saw was assessed and compared to the classical planning and freehand cutting method. The pre-operative plan was transferred with high accuracy. Three-dimensional-printed patient-specific guides improve the accuracy of osteotomies and bony resections in an experimental setup compared to conventional freehand methods. The improved accuracy is related to (1) a detailed and qualitative pre-operative plan and (2) an accurate transfer of the planning to the operation room with patient-specific guides by an accurate guidance of the surgical tools to perform the desired cuts.